Application of the interlearning groups proposal -GIA- in the teaching performance in an educational institution in Tacna - Ayquipa Granda, María del Carmen (2021)
Basic, explanatory research. It seeks to determine the impact of the application of the strategy "Interlearning Groups" (GIA) on the performance of teachers in an educational institution in Tacna.  We worked with a population of 62 study units: 27 primary school teachers and 35 secondary school teachers. Information was collected through two questionnaires: one to collect information on the application of the GIA strategy, and the other to collect information on the level of teacher performance. It has been determined that the degree of application of the GIA strategy in the Manuel A. Odría educational institution has been optimal at 51.61%. However, indicators such as: distribution of time spent (32.26%), organization (46.77%), resources used (33.87%) and level of control (40.32%) are below this percentage. To establish the relationship between the variables, Spearman's Rho test was applied, the coefficient obtained was 0.120 and a p-value equal to 0.353 (p-value > 0.05), which represents a practically null correlation between the variables under study. Finally, the results found allow us to conclude that the application of the strategy "Interlearning Groups" (GIA) had a moderate impact on the teaching performance in the educational institution Manuel A. Odría in 2018